СОNTINUOS PROFESSIONAL EDUCATION AS A WAY TO PROVIDE HIGHER EDUCATION LIBRARIES WITH QUALITATIVELY NEW ADVANCED SKILLED STAFF - Popovich, Inna Anatoliivna; Kucherenko, Yuliia V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This article presents the experience of Scientific and Technical Library in Dnipropetrovsk National University of Railway Transport named after academician V. Lazaryan concerning employees professional development, especially the work of ―Information specialist school‖.